Demographic development of Piran with an emphasis on the (informal) population census of the Piran local community in 2020 - Pletikosić, Ivica (Journal for Geography, 2026)
This paper has two objectives. The first is to present the demographic development of the oldest continuously inhabited settlement in the territory of present-day Slovenia. The second objective is to identify the discrepancy between the number of permanently registered residents in the town and the number of people who actually reside or live there. The number of people actually residing in Piran is significantly lower than the number of permanently registered residents, as official statistical data do not reflect the city’s real demographic situation. The discrepancy has increased in recent decades, mainly due to the growth of secondary residences. Despite a formally stable population size, Piran is facing a long-term process of depopulation.